Robust Roll-Over Avoidance Control for a Laboratory Vehicle. Issue 25 (2018) - Shraiber, Arie; Gutman, Per-Olof; Shima, Tal
Abstract: A Multiple Input Multiple Output (MIMO) robust roll-over avoidance control algorithm that prevents a laboratory vehicle from rolling over due to disturbances and extreme driving maneuvers is presented. The control signals are an auxiliary steering angle and an auxiliary vehicle velocity reference which are added to the steering angle and vehicle velocity reference commanded by the driver or the driving algorithm. The robust linear control law is designed by Quantitative Feedback Theory (QFT), utilizing an uncertain linear MIMO vehicle model identified from a measurement based non-linear vehicle model. The algorithm is tested in simulations and then on the actual laboratory vehicle with satisfactory performance.